MARKETING TECHNOLOGIES OF INCREASE VOLUME OF ACTIVITY IN INSURANCE BUSINESS - HOLIAS, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study, the focus of attention is concentrated around the activity and development of insurance business entities. Ways and means of increasing the volume of activity of insurance organizations are analyzed. The possibilities of using marketing technologies for such purposes are considered. Based on these principles, the purpose of the research is to generalize promising marketing technologies for increasing the volume of activity in the insurance business. It has been established that marketing technologies are related to the implementation of activities according to such vectors as rational pricing, active work with the target market segment (consumers of services, existing and prospective), improving services and increasing their quality level, stimulating the promotion of services. The miscalculations that are allowed as a result of an incorrect assessment by the insurance company’s management of consumer expectations, an incorrect perception of the insurance company’s management about the quality of services, low quality of service, and unreliable advertising information are determined. The peculiarities of the implementation of the so-called "quality wheel in the service sector" have been determined. It is shown that technological marketing tools aimed at increasing the volume of insurance services provide the following actions according to the directions of the implemented policy: improvement of services (strengthening the image of the company and its services; ensuring compliance with the image of the company, the volume and quality of service provision, the quality of staff work); improvement of price characteristics of services (formation of pricing policy based on the principle of "Correspondence of quality and image +", which means that the price should correspond and be slightly overestimated so that clients understand that the insurance company provides a high level of service quality and "knows its price"); development of communications (establishment of a digital communication system with existing and potential clients; creation of a virtual communication environment; active use of progressive Internet marketing tools); scaling up the distribution of services (differentiated application of the following strategies: network based on the development of the infrastructure for the provision of insurance services, including on the basis of franchising; multi-service due to the expansion of the range of services provided; multi-segment through promotion into new market segments; mixed, when development practices are combined infrastructure, expanding the range of services and entering new market segments).